2019
DOI: 10.3390/jcm8071075
|View full text |Cite
|
Sign up to set email alerts
|

Could Neutrophil-to-Lymphocyte Ratio (NLR) Serve as a Potential Marker for Delirium Prediction in Patients with Acute Ischemic Stroke? A Prospective Observational Study

Abstract: Delirium is an acute brain disorder that commonly occurs in patients with acute ischemic stroke (AIS). Pathomechanism of delirium is related to the neuroinflammatory process and oxidative stress. Search for readily available diagnostic marker that will aid clinicians in early identification of delirium is ongoing. The aim of this study was to investigate whether neutrophil-to-lymphocyte ratio (NLR) could serve as a potential marker for delirium prediction in patients with AIS and to find an easy diagnostic too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 39 publications
(47 reference statements)
4
60
1
Order By: Relevance
“…Episodic and chronic migraine various inflammatory biomarkers and migraines have been investigated by several researchers [3,19,20]. Many researchers have investigated the relationships between the features of headaches and inflammation using hematologic parameters [3,6,10,13,[21][22][23]. The main goal of these studies is to evaluate the inflammatory processes using hematological markers and to investigate the association of these markers with clinical parameters of headaches, and their utility in discriminating headache syndromes from other diseases [10,24].…”
Section: The Results Of the Comparisons Of Nlr Between The Patient Grmentioning
confidence: 99%
See 1 more Smart Citation
“…Episodic and chronic migraine various inflammatory biomarkers and migraines have been investigated by several researchers [3,19,20]. Many researchers have investigated the relationships between the features of headaches and inflammation using hematologic parameters [3,6,10,13,[21][22][23]. The main goal of these studies is to evaluate the inflammatory processes using hematological markers and to investigate the association of these markers with clinical parameters of headaches, and their utility in discriminating headache syndromes from other diseases [10,24].…”
Section: The Results Of the Comparisons Of Nlr Between The Patient Grmentioning
confidence: 99%
“…However, even when WBC is within normal limits, an increased neutrophil to lymphocyte ratio (NLR) may indicate inflammation and inflammation-related pathologies [4]. The NLR has been used in the evaluation and prognostication of various diseases, including coronary artery diseases, malignancies, rheumatologic diseases, and neurological diseases [5][6][7][8][9][10][11][12]. Few studies have investigated the value of this marker in the evaluation of migraineurs [8,10,13].…”
Section: Introductionmentioning
confidence: 99%
“…A study based on the white cells-derived markers (NLR, PLR, and PWR) seems promising, and thanks to their effectiveness and the ease of obtaining the results, they may become a helpful factor in the diagnosis and monitoring of delirium after cardiac surgery [ 61 ]. It has also been proposed to use NLR as a potential marker for delirium prediction in patients with other medical problems (i.e., acute ischemic stroke) [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…Egberts et al [42] found that in a cohort of acutely ill elderly patients, a raised NLR was an independent predictor of delirium. Additionally, Kotfits et al [43] stated that an increased NLR is significantly associated with increased risk of delirium in patients with acute ischemic stroke. The results of our study are consistent with these increase its permeability, cytokines then migrate across the BBB and activate microglia which will produce reactive oxygen species, the accumulation of cytokines and reactive oxygen species in brain may lead to the process of oxidization and inflammation and eventually result in neurodegeneration [7,46].…”
Section: Discussionmentioning
confidence: 99%